2007
DOI: 10.1016/j.acra.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Monitoring Response to Chemotherapy of Human Diffuse Large B-Cell Lymphoma Xenografts in SCID Mice by 1H and 31P MRS

Abstract: Rationale and Objectives-A reliable non-invasive method for in vivo detection of early therapeutic response of non-Hodgkin's lymphoma (NHL) patients would be of great clinical value. This study evaluates the feasibility of 1 H and 31 P magnetic resonance spectroscopy (MRS) for in vivo detection of response to combination chemotherapy of human diffuse large B-cell lymphoma (DLCL2) xenografts in SCID mice.Materials and Methods. C-ombination chemotherapy with Cyclophosphamide, Hydroxydoxorubicin, Oncovin, Prednis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Although the mitochondrial proteins and their functional processes have been widely studied (9)(10)(11), little is known about mitochondrial proteome alterations of various cells or fractions after exposure to various conditions. Furthermore, although the effects of ADR on NHL have been investigated (12,13), most studies have focused only on evaluating single-protein changes and none on the total cellular proteome or the mitochondrial proteome. We selected Raji cells for study because Raji cells can serve as a model for human lymphomas with mutant p53 and increased BCL2 expression, which are commonly present in patients with NHL and are considered a source of chemotherapy failure in patients whose disease is chemoresistant (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mitochondrial proteins and their functional processes have been widely studied (9)(10)(11), little is known about mitochondrial proteome alterations of various cells or fractions after exposure to various conditions. Furthermore, although the effects of ADR on NHL have been investigated (12,13), most studies have focused only on evaluating single-protein changes and none on the total cellular proteome or the mitochondrial proteome. We selected Raji cells for study because Raji cells can serve as a model for human lymphomas with mutant p53 and increased BCL2 expression, which are commonly present in patients with NHL and are considered a source of chemotherapy failure in patients whose disease is chemoresistant (14).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to assess the reproducibility of total cholineto-water ratios in xenografts of other tumor cell lines that may exhibit more necrosis and/or other tissue heterogeneities than U87MG tumors in the linear growth phase. Further, although the longest interval between scans was just 7 days in the present study, previous studies have indicated that 7 days is a sufficiently long interval to observe changes in metabolite ratios in xenografts produced by interventions including radiation (37) and oncolytic drugs (eg, [38][39][40].…”
Section: Discussionmentioning
confidence: 67%
“…5, (Street et al , 1997; Darpolor et al , 2011a; Koutcher et al , 2000), and without 1 H decoupling and significant NOE enhancement (Fig. 6, (Huang et al , 2007)).…”
Section: 0 Preclinical 31p Mr Spectroscopy Of Solid Tumorsmentioning
confidence: 88%